The Types of Professionalism in Architectural Education - Kapustin, Petr (project baikal, 2017)
Being rebuilt or renovated, architectural profession does not need to ‘move closer to practice’. On the contrary, it should break away from it. ‘Architectural professionalism’ is not a homogeneous or inert body. It split up long ago. It is not a single profession, but a complex heterogeneous field that demands multilayer strategies.